Importancia de la motivación para el aprendizaje de matemáticas en los niños y niñas del 4to año de educación general básica en el Colegio Militar Patría Nro. 13 perteneciente al sector Guaytacama ubicado en la ciudad de Latacunga en el periodo académico 2014-2015 - Vilcaguano Vera, Ana del Rocío (2015)
This investigation is very important. The motivation for learning is not recent, it has been a concern since decades before, and even now for the teaching-learning process. The principal objective of this thesis was: to propose motivation strategies for learning mathematics in children of the fourth year belonging for Basic General Education of COMIL Patria Nro.13. The problem investigated was: What is the importance of motivation for learning mathematic? The methods used were: inductive and deductive in the research field, for getting conclusions there were used hypothetical-deductive method, empirical-analytic for analysis on the site of the facts in addition, analytic-synthetic for a thorough knowledge of the subject matter The results of this investigation show that math classes are tedious hours, It cause disinterest in performing mathematical exercises and also that determinate the deficiency of educational resources using. The contribution of this work was the design of mathematical exercises thought the using of the Constructor Atenex Digital Education Program, in which children can learn while playing: It consists of ten workshops, related to different curricular blocks and textbook of the fourth degree of basic general education.